Influence of the fixed combination of glycine with thiotriazoline on energy metabolism parameters in brain in conditions ofexperimental cerebral ischemia - Kucherenko, L.; Belenichev, I. F.; Mazur, I.; Khromylova, O.; Parniuk, N.; Кучеренко, Людмила Іванівна; Бєленічев, Ігор Федорович; Мазур, Іван Антонович; Хромильова, Ольга Володимирівна; Парнюк, Н. В. (My University, 2018)
The perspective direction of primary neuroprotection in cerebral ischemia is the correction of the imbalance of excitatory and inhibitory neurotransmitter systems by activating natural inhibitory processes. There is evidence of the ability of anti-oxidant thiotriazoline to potentiate the therapeutic effect of neuro-metabolic cerebroprotectors. Therefore, it is interesting to create a new combined drug based on glycine and thiotriazoline. The purpose of this study is to investigate the effect of glycine, as well as its combination with thiotriazoline, on the parameters of hydrocarbon-energy processes and oxidative metabolism under the conditions of simulation of acute cerebrovascular disorder (ACVD). Material and Method: To create ACVD, a classic model consisting of simultaneous ligation of common carotid arteries was used in 50 Wistar male rats. All drugs were administered intraperitonally for four days starting with anesthesia recovery of rat groups. The content of adenyl nucleotides, pyruvate, lactate, malate, isocitrate and activities of succinate dehydrogenase, cytochrome C-oxidase, glutamate decarboxylase, GABAtransferase were determined in the homogenates of brain cortex by biochemical methods. Result and Discussion: Our results showed that the combination of glycine with thiotriazoline is better than such reference drugs like pyracetam and glycine, according to degree of effect on the indicators of energy metabolism of the brain, indicating the relevance of further study of the proposed combination.
Keywords: glycine; neuroprotective action; stroke; thiotriazoline; transmitter amino acids